Clinical efficacy observation of repetitive transcranial magnetic stimulation combined with auditory integration training in children with ASD - Hao, Qing-hong; Wang, Jin-ying; Yang, Jin-di; Tong, Yao; Xiao, Lei; Zeng, Xiao-qin; Li, Wei; Hu, Su-fen; Lv, Zhi-hai (Frontiers in Psychiatry, 2026)
BackgroundAutism spectrum disorder (ASD) has become a major public health issue of global concern and has attracted the attention of researchers in recent years. Due to the high incidence and persistent lifelong dysfunction of children with ASD, exploring active and effective intervention strategies plays a key role in their prognosis. Repetitive transcranial magnetic stimulation (rTMS) and auditory integration training (AIT) are both promising neuromodulation methods and play an important role in clinical intervention in children with ASD. This study aims to explore the clinical effectiveness of rTMS and AIT combined intervention compared with single intervention through randomized controlled experiments, and provide scientific basis for clinical intervention in ASD.MethodsA total of 60 participants with ASD were randomly assigned to the study group (rTMS combined with AIT) and the control group (rTMS) in a 1:1 ratio, with 30 participants in each group. The outcome indicators were the Autism Behavior Checklist (ABC), the Childhood Autism Rating Scale (CARS), the Strengths and Difficulties Questionnaire (SDQ), and the Repetitive Behavior Scale-Revised (RBS-R). Clinical data were collected at baseline and after intervention. Data were processed and analyzed by SPSS.ResultsAfter 12 weeks of intervention, the total scores of ABC, CARS, SDQ and RBS-R in the two groups were significantly improved compared with those before intervention (P < 0.05). Compared with the control group, after 12 weeks of intervention, the total scores of ABC and CARS, as well as the total scores and some dimensions of SDQ and RBS-R were significantly improved (P < 0.05).DiscussionThe intervention therapy of rTMS combined with AIT has significant efficacy in children with ASD, which can significantly improve the core symptoms and emotional behavioral problems of children with ASD. This method is worthy of being promoted and applied in clinical practice.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=225665, identifier ChiCTR2400082706.